Five Year Plan Assam District and Subdivisional Series United Mikir and North Cachar Hills - Government of Assam (Government of Assam, 1955)
The Assam Five-Year Plan (1951-56) for the United Mikir and North Cachar Hills districts represents a comprehensive regional development initiative aimed at enhancing social welfare, economic stability, and infrastructure. Structured under the broader state-wide framework outlined in the 1954 Broad Outline and Progress Report, the plan emphasizes targeted interventions through General State Plans, Expansion Plans, Tribal Area Development under Article 275, Community Projects, and Local Development Works. Total financial provision for these districts was approximately Rs. 58.195 lakhs, with Rs. 15.797 lakhs expended in the first three years, reflecting measured progress in resource utilization. Key sectors include agriculture and irrigation, benefiting thousands of acres through minor irrigation schemes, education through the construction of schools and teacher training programs, and health services via dispensaries and hospitals to improve medical access. Institutional mechanisms, particularly Subdivisional Development Committees led by district officials, facilitate planning, monitoring, and collaboration with local communities, ensuring participatory implementation. The plan demonstrates a strategic approach to upliftment by addressing local needs, promoting economic productivity, and fostering community engagement, thereby laying the foundation for sustainable growth and improved living standards in the United Mikir and North Cachar Hills regions.
Department of Planning and Development Government of Assam
Department of Planning and Development Government of Assam
Keywords: Assam Five-Year Plan; United Mikir Hills; North Cachar Hills; Subdivisional Development Committees; Agriculture; Irrigation; Education; Health Services; Community Projects; Tribal Area Development; Local Development Works; Infrastructure